Success Rate of Phacoemulsification for Cataract in Patients with High-Degree Myopia in National Eye Center Cicendo Eye Hospital Bandung, Indonesia - Budiman, Nadia Khairina; Knoch, Andrew Maximilian; Susanti, Yuni (Althea Medical Journa, 2014)
Background: Phacoemulsification is one of the procedures performed in cataract with high-degree myopia patients. Patients with high-degree myopia have a higher risk for postoperative complications due to phacoemulsification which affects their visual acuity. These patients also have higher manifest refraction compared to cataract without high-degree myopia. This study aims to evaluate the success rate of phacoemulsification for cataract in patients with high-degree myopia in National Eye Center, Cicendo Eye Hospital Bandung, Indonesia.Methods: A descriptive study was performed by collecting data from medical records on phacoemulsification in cataract patients with high-degree myopia at the National Eye Center, Cicendo Eye Hospital, during JanuaryâDecember 2011. There were 79 cases out of 136 cases that met the inclusion criterias, those were cataract patients with high-degree myopia who underwent phacoemulsification and patients who did regular follow up visits. Data were analyzed using computer. Results: The results showed that from 79 cases, 44(55.7%) cases involved female patients. Visual acuity after phacoemulsfication increased gradually at 1â2 months follow-up. Eighty one percent cases have been corrected at best with a visual acuity of higher than 6/18. No intraoperative complication occurred in 96.2% of the cases but 3.8% cases had zonular dialysis and vitreous prolaps as intraoperative complication. Meanwhile, corneal edema as postoperative complications occurred in 58.3% of the patients. A total of 17 (21.5%) cases had manifested refraction more than Â±2.00 diopter.Conclusions: Phacoemulsification in cataract with high-degree myopia resulted in good visual acuity and minimal complications. However, extreme manifest refraction still occurs in several patients [AMJ.2014;1(1):12â6]Keywords: cataract, high-degree myopia, phacoemulsificationÂ Tingkat Keberhasilan Fakoemulsifikasi pada Penderita Katarak yang Disertai Miopia Tinggi di Pusat Mata Nasional Rumah Sakit Mata Cicendo, Bandung, IndonesiaLatar Belakang: Miopia tinggi diketahui berhubungan dengan terjadinya katarak. Kasus-kasus tersebut memiliki risiko komplikasi fakoemulsifikasi yang lebih tinggi dibandingkan katarak biasa dan dapat memengaruhi tajam penglihatan serta kualitas hidup pasien sehingga dibutuhkan evaluasi mengenai tingkat keberhasilan fakoemulsifikasi. Penelitian ini bertujuan untuk mengetahui gambaran tajam penglihatan pascabedah, komplikasi,dan refraksi manifes pada penderita katarak disertai miopia tinggi yang menjalani prosedur fakoemulsifikasi.Metode: Penelitian dilakukan dengan metode deskriptif dengan pengambilan data sekunder dari rekam medis di Pusat Mata Nasional Rumah Sakit Mata Cicendo pada JanuariâDesember tahun 2011. Ada 79 kasus dari 136 kasus yang memenuhi kriteria inklusi yaitu penderita katarak dengan derajat miopia tinggi yang menjalani fakoemulsifikasi dan rutin datang berobat. Data diolah menggunakan program komputer.Hasil: Hasil penelitian menunjukkan bahwa tajam penglihatan tanpa koreksi 1 hari pascabedah fakoemulsifikasi pada 49,4% kasus dibawah 6/60 yang berangsur membaik pada kunjungan 1â2 bulan. Sebanyak 81,0% kasus memiliki tajam penglihatan dengan koreksi terbaik diatas 6/18. Terdapat 96,2% kasus yang tidak mengalami komplikasi intrabedah. Edema kornea sebagai komplikasi 1 hari pascabedah fakoemulsifikasi cukup banyak terjadi yaitu sebanyak 45,6%. Pada penelitian ini didapatkan refraksi manifes dengan rentang -12.00 sampai +10.00 dioptri, 78,5% berada dalam rentang Â±2.00.Simpulan: Prosedur pada katarak miopia tinggi menunjukkan hasil penglihatan yang baik dan komplikasi minimal , tetapi pada katarak yang disertai miopia tinggi masih terdapat pasien yang memiliki refraksi manifes yang cukup berat.Kata kunci: Fakoemulsifikasi, katarak, miopia tinggi